Childfree in the perspective of Manhaj Tarjih Muhammadiyah: An analytic study of childfree with bayani, burhani, and irfani approaches - Putri, Khulanah Sutarno; Daib Insan Labib, Muhammad Alfreda (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
The decision not to have children (also known as childfree) is a Western lifestyle that is currently being debated. The concept is regarded as unnatural, contrary to human nature, and outside of the values held by society, particularly Indonesian. From an Islamic perspective, the concept of childfree opposes the shari'ah's goals (maqasid al syari’ah) namely hifzu an-nasl (protecting of offspring). This study focused on discussing about the concept of childfree based on the perspective of Manhaj Tarjih Muhammadiyah. Three basic questions discussed were 1) the history and background of the concept of childfree, 2) the perspective of the Muhammadiyah Tarjih and Tajdid Council and 3) the concept of childfree in the perspective of Manhaj Tarjih Muhammadiyah? The method used in this research is a qualitative method using library research through several primary sources such as the book "Childfree and Happy" by Victoria Tunggono, the book of "Manhaj Tarjih Muhammadiyah" written by Syamsul Anwar, Decisions of the Tarjih National Deliberation Muhammadiyah XXV in Jakarta and other secondary sources in the form of books, books, journals, or previous research. Based on research related to the concept of childfree, then analyzed using the bayani, burhani, and irfani approaches and a collection with hierarchical assumptions, namely basic values (al-qiyām al-assiyyah), general principles (al-uṣūl al-kulliyah) and practical legal provisions (al-ahkam al-far'iyyah), it can be concluded that the concept of childfree (the decision to not have children) is not justified in Islam.